Investigation of spinal dynamic stabilization device using finite element method - Zhou, Yuanli (2008)
A FE model of lumbar spine was developed and validated, which was used to evaluate biomechanical effect of new dynamic stabilization device (FlexPLUS). The FlexPLUS system was more flexible than rigid rod system but not flexible enough to preserve motion and restore natural load sharing ability of the operated segment.